Does developing multiple-choice Questions Improve Medical Students' Learning? A Systematic Review. Issue 1 (31st December 2022) - Touissi, Youness; Hjiej, Ghita; Hajjioui, Abderrazak; Ibrahimi, Azeddine; Fourtassi, Maryam
ABSTRACT: Practicing Multiple-choice questions is a popular learning method among medical students. While MCQs are commonly used in exams, creating them might provide another opportunity for students to boost their learning. Yet, the effectiveness of student-generated multiple-choice questions in medical education has been questioned. This study aims to verify the effects of student-generated MCQs on medical learning either in terms of students' perceptions or their performance and behavior, as well as define the circumstances that would make this activity more useful to the students. Articles were identified by searching four databases MEDLINE, SCOPUS, Web of Science, and ERIC, as well as scanning references. The titles and abstracts were selected based on a pre-established eligibility criterion, and the methodological quality of articles included was assessed using the MERSQI scoring system. Eight hundred and eighty-four papers were identified. Eleven papers were retained after abstract and title screening, and 6 articles were recovered from cross-referencing, making it 17 articles in the end. The mean MERSQI score was 10.42. Most studies showed a positive impact of developing MCQs on medical students' learning in terms of both perception and performance. Few articles in the literature examined the influence of student-generated MCQs on medical students learning. Amid some concerns about time and needed effort, writing multiple-choice questions as a learning method appears to be a useful process for improving medical students' learning.